Efforts of Bhabinkamtibmas in Preventing Sexual Assault Through Door-to-Door Counseling - Kabarek, Andrian (Advances in Police Science Research Journal, 2024)
The crime of molestation in the Ciamis District Police Law area is a high crime rate increase, this should not have happened because children are an inseparable part of human survival, growth and development and are entitled to protection from violence and discrimination. Ciamis Regional Police prioritizes preemptive measures to prevent the crime of sexual abuse. The purpose of this study is to describe the implementation of the prevention of the crime of sexual abuse by Bhabinkamtibmas at the Ciamis Regional Police Station, and find out the factors that cause the crime of sexual abuse against a child at the Ciamis Regional Police Station. In this study the implementation of the task of Bhabinkamtibmas in preventing acts of sexual abuse by using role theory, crime prevention theory and management theory. And by paying attention to its suitability with the concept of Community Development. This research was conducted with a qualitative approach and type of field research was conducted with a qualitative appeoach and type of field research. With data collection techniques uses include data reduction, data presentation and drawing conclusions. The results of this study and conclusions of this study show that based on data obtained and interviews with the Head of the District Police, Kasat Binmas, Kanit Bintibmas, the Bhabinkamtibmas, PPA Kanit, perpetrators of the crime of sexual abuse of children, and community leaders that the members of Bhabinkamtibmas are still not thoroughly carrying out the elements management and roles that have been carried thoroughly carrying out the elements management and roles that have been carried out have not been carried out evenly. The factors causing the occurrence of ceiminal acts of sexual abuse are internal and external factors. Internal factors consist of limited personnel.